Identification of Plants Diversity Composing Peatland Vegetation After Forest Fires in Mount Bongkok Reserved Forest - Ivan Eldes Dafrita; Tesa Manisa; Novi Nurmayanti (Universitas Labuhanbatu, 2024)
This research aims to identify the diversity of plants that make up peatland vegetation in the Mount Bongkok Reserved Forest after forest fires. This research is a quantitative qualitative descriptive research. The method used is the plot method. Area of observations were determined using purposive sampling with the assumption that the existing vegetation could represent the entire community. The sampling size/intensity (IS) used was 5% of the total area of 100 Ha, so the total sampling area was 5 hectares. The sampling location was divided into 50 observation plots with a size of 25x40m each plot. The results showed that Ubah (Syzygium sp.) and Pulai (Alstonia pneumatophore) plants were found at all sampling points. Geronggang plants (Cratoxylon arborescens) and Jelutung plants (Dyera lowii) were found at more than 50% of sampling points. These four plants are plants that are suitable for habitats in peatlands. This shows that this plant is suitable for growing in the peatland habitat and can be used for peatland conservation